The clausal syntax of German Sign Language A cartographic approach (Volume 5) - Bross, Fabian (Language Science Press, 2020)
This book presents a hypothesis-based description of the clausal structure of German Sign Language (DGS). The structure of the book is based on the three clausal layers CP, IP/TP, and VoiceP. The main hypothesis is that scopal height is expressed iconically in sign languages: the higher the scope of an operator, the higher the articulator used for its expression. The book was written with two audiences in mind: On the one hand it addresses linguists interested in sign languages and on the other hand it addresses cartographers.